Paradox between neoliberal urban redevelopment, heritage conservation, and community needs: Case study of a historic neighbourhood in Tianjin, China. (February 2019) - Wang, Xue; Aoki, Nobuo
Abstract: Today, China's inner-city redevelopment has evolved into the neoliberalism phase, which is characterized by market orientation, privatization, commodification, and short-term returns; this phase generally involves massive demolition and eviction, resulting in serious conflicts between land-based economic growth, heritage conservation, and social justice. The local community is susceptible to social, cultural, and economic impacts of redevelopment, as well as heritage conservation activities. Thereby, the perspectives of residents on these two components of the urban development agenda help to re-examine the demolition–conservation controversy from the perspective of social well-being. Based on an in-progress case in Tianjin, this study clarifies the multi-faceted paradox posed by the demolition–conservation dichotomy at the locality level. Further, the study performs an ex-ante investigation on the needs, concerns, and attitudes of the local community and dissects related contradictions with the local government's rationale for redevelopment, which is a prerequisite for facilitating responsive and democratic urban planning. Highlights: The government–developer coalition disrupts locality-level heritage conservation. Entrepreneurial governments shape urban landscapes by advancing pro-growth agendas. The growth-oriented spatial politics cause residents the threat of displacement. Due to their need for better housing, residents favour demolition over conservation.